Assessing the effects of supplementary cementitious materials on concrete properties:a review - Almotaseembillah Ahmed (Discover Civil Engineering)
Abstract Sustainability has become an increasingly important goal, especially in developing countries where the focus is on protecting the environment and improving public health. A major environmental concern is the production of carbon dioxide, with cement manufacturing being a significant contributor. Cement, a key ingredient in concrete the second most used material worldwide after water plays a major role in the rising CO2 emissions each year. This situation highlights the urgent need for new research to reduce the environmental impact of cement production. One promising approach to addressing these challenges is the use of supplementary cementitious materials (SCMs). SCMs have the potential to partially replace cement in concrete mixes, which can reduce CO2 emissions, decrease air pollutants, and save non-renewable resources. However, adding SCMs to concrete can lead to changes in its properties, where some may decrease compared to conventional concrete, while others may improve. This research examines various SCMs and evaluates their impact on the strength, workability, and durability of concrete. It also includes a detailed analysis using scanning electron microscopy (SEM) to study the microstructure. SCMs such as silica fume (SF), metakaolin (MK), and ground granulated blast furnace slag (GGBFS) significantly improve compressive strength, chloride penetration resistance, and microstructural density at certain replacement levels. Fly ash (FA) supports long-term strength development, while agricultural by-products like rice husk ash (RHA) and palm oil fuel ash (POFA) contribute to durability improvements when used carefully. The study underscores the importance of particle size, replacement rates in optimizing SCM performance, balancing workability, cost, and environmental benefits.